ANALSIS BIOAKUMULASI LOGAM BERAT TIMBAL (Pb) DAN ARSEN (As) PADA IKAN BANDENG (Chanos chanos) DI TAMBAK TRADISIONAL DESA BANJAR KEMUNING, KABUPATEN SIDOARJO - Sapto Andriyono; Ainun Ma’rifa; Nina Nurmalia Dewi (Jurnal Perikanan Unram, 2024)
Sidoarjo has a large aquaculture area, but it is a dense city with rapid industrial development. Thus, aquaculture activities such as milkfish, which is a leading commodity, are threatened by water pollution by waste and decreased water quality. Related to this, the purpose of this study is to examine the content of heavy metals lead (Pb) and arsenic (As) in milkfish (Chanos chanos). These metals are substances that have the potential to pollute river aquaculture water sources because they are found in many industrial and household wastes such as paint waste, batteries, insecticides, and pesticides, which are also likely to accumulate in aquatic biota.  This study used observation and purposive sampling methods for sampling and measuring water quality, while testing heavy metals Pb and As with ICP-MS, and quantitative descriptive data analysis of several parameters including Geo-Accumulation Index (Igeo), Contamination Factor (CF), and Bio-Concentration Factor (BCF). Based on the results of the study, Pb content in water at the three points was not detected / ND. As in water obtained an average of 0.030 mg/l. While, lead in sediment the average value is 7.84 mg/kg, and 3.30 mg/kg for As. Pb in milkfish was found to average 0.082 mg/kg, and As was 0.277 mg/kg. Overall, Pb and As at the three points were still below the established threshold. However, the average concentration of As metal in water has exceeded the quality standard of KepMen LH No. 51 Th. 2004.  Based on the calculation data of the Igeo index, CF, and BCF, the accumulation rate is low so that the level of pollution and contamination is considered safe. Water quality measurements are said to be good for milkfish aquaculture growth at all three points because they meet the optimal value standards for salinity, pH, DO, brightness and temperature.